Density currents reduce nitrous oxide emissions in a tributary bay of Three Gorges Reservoir. (15th February 2021) - Guo, Xiaojuan; Liu, Jia; Liu, Defu; Yang, Zhengjian; Xiao, Shangbin; Lorke, Andreas
Highlights: High-resolution mapping of dissolved N2O concentration in a deep reservoir. Surface water was supersaturated with N2O at both maximum and minimum water level. Bidirectional density currents formed strong vertical N2O concentration gradients. Density currents reduced the N2O emission potential per unit area. Abstract: Reservoirs are a significant source of the potent greenhouse gas nitrous oxide (N2 O), but there are few data on N2 O in the world's largest reservoirs and limited understanding of the factors controlling their emission rates. Here we analyzed high-resolution measurements of dissolved N2 O concentrations and fluxes in a typical tributary bay of Three Gorges Reservoir. The surface water was oversaturated in N2 O during both low and high water level (8.6 -16.4 nmol/L, 107% - 180% saturation) and N2 O fluxes varied nearly tenfold (0.2 and 1.6 μmol/(m 2 h)). Dissolved N2 O concentrations were characterized by pronounced vertical gradients, which were controlled by bidirectional density currents. The river water with high concentrations entered the bay as an underflow along the riverbed, the upper part of the water column was formed by intrusive backwater of Three Gorges Reservoir having significantly lower N2 O concentrations. In consequence, the N2 O emission potential of the impoundment was reduced compared to pre-impoundment conditions. These results reveal the importance of hydraulic conditions on N2 O emission from large reservoirs and suggest that flow regulation can be a potential tool for mitigating greenhouse gas emissions from manmade impoundments.